Program Kemitraan dalam Pengembangan Pangan Lokal Singkong Krispi Rumput Laut untuk Meningkatkan Pendapatan Masyarakat - Tati Atia Ngangun; Ismael Marasabessy (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Partner of the community partnership program on this study is a group of cassava chips processing located in the village of Ibra, Southeast Maluku district. Partners can be classified into economically productive societies, but they still face many problems in the production and marketing process. The purpose of this activity was to increase the income of the cassava chip processing group partners, and to increase the added value of cassava root by adding seaweed into high fiber cassava chips. The activity was carried out in three stages, firstly producing cassava flour with an improved press method, secondly producing cassava plates, and thirdly producing cassava krispi seaweed chips(SKRL). The results of the activity showed that SKRL products were quite attractive to consumers. With the improvement of the form, taste and packaging of SKRL had become one of the typical souvenirs of the Kei community. The marketing strategy adopted was to increase packaging using two types of packaging, namely primary packaging with propilen plastic (PP) and secondary packaging using paper boxes. Seaweed cassava produced was very preferred by consumers because it tastes good and crispy. The use of a screw press produced cassava chips with very low HCN levels so it is very safe to consume. The partner's income increased, the sales during the 6 months of activities reached 600 boxes with a value of IDR 10,000,000.